Inter- and intra-patient variability of raltegravir pharmacokinetics in HIV-1-infected subjects - Cattaneo, D.; Gervasoni, C.; Meraviglia, P.; Landonio, S.; Fucile, S.; Cozzi, V.; Baldelli, S.; Pellegrini, M.; Galli, M.; Clementi, E. (Journal of antimicrobial chemotherapy, 2012)
Limited studies in healthy volunteers and in HIV-1-infected patients have shown that raltegravir pharmacokinetics are characterized by high inter-patient variability. Only scanty data are, however, available on intra-patient raltegravir variability. The present study was designed to evaluate in parallel the inter- and intra-patient variability of raltegravir pharmacokinetics in HIV-1-infected patients during routine therapeutic drug monitoring (TDM). Fifteen HIV-infected patients treated with highly active antiretroviral therapy containing 400 mg of raltegravir twice daily were included in the study. Pharmacokinetic evaluations were performed during two consecutive visits. Only patients given raltegravir for at least 1 month and with no changes in antiretroviral and concomitant therapy between the two pharmacokinetic evaluations were considered. Raltegravir plasma concentrations were determined by a validated HPLC method. Blood samples were collected at 0, 1, 2, 3 and 4 h after the morning drug dose. Raltegravir AUC(0-12) was estimated using a recently developed algorithm. The pharmacokinetic evaluation was repeated after an average of 52 ± 68 days. Raltegravir AUC(0-12) values ranged from 1495 to 49 051 ng · h/mL. The main finding was that intra-patient variability was a large component of the overall variability in raltegravir pharmacokinetics. In some instances the difference between raltegravir AUC(0-4) and AUC(0-12) measured in the same patient during two consecutive evaluations exceeded 110% and 75%, respectively. The pharmacokinetics of raltegravir in HIV-1-infected subjects are characterized not only by inter-patient variability but also by high intra-patient variability. This condition limits the application of TDM for raltegravir, and might potentially affect patient outcome.